Impact of concomitant chemoradiation on survival for patients with T1‐2N1 head and neck cancer. Issue 9 (21st December 2016) - Zumsteg, Zachary S.; Kim, Sungjin; David, John M.; Yoshida, Emi J.; Tighiouart, Mourad; Shiao, Stephen L.; Scher, Kevin; Mita, Alain; Sherman, Eric J.; Lee, Nancy Y.; Ho, Allen S.
Abstract : BACKGROUND: Single‐modality radiotherapy is considered a standard‐of‐care option for certain stage III, T1‐2N1 head and neck squamous cell carcinomas (HNSCCs). The role of concomitant chemoradiation is not well established because there have been no studies comparing chemoradiation with radiation alone in this population. METHODS: This study analyzed patients in the National Cancer Data Base with cT1‐2N1M0 invasive squamous cell carcinomas of the oropharynx, larynx, and hypopharynx who were diagnosed between 2004 and 2012 and were undergoing definitive radiation. Patients who were undergoing surgery before radiation with unknown follow‐up or for whom either the receipt or timing of chemotherapy was unknown were excluded. RESULTS: In all, 5030 patients with T1‐2N1 oropharyngeal, laryngeal, or hypopharyngeal cancer were included. The median follow‐up was 56.8 months (95% confidence interval [CI], 55.7‐58.6 months). Overall, 68% of the patients received concomitant chemoradiation (CCRT). The use of CCRT significantly increased during the time period of this study from 53% in 2004 to 78% in 2012 ( P < .001). CCRT was associated with improved overall survival (OS) in comparison with radiation alone in a multivariate analysis (hazard ratio [HR], 0.80; 95% CI, 0.72‐0.88; P < .001). In propensity score–adjusted analyses, CCRT remained significantly associated with improved OS, with 5‐year OS rates of 63.5% (95% CI, 60.7%‐66.2%) and 55.6% (95% CI, 52.7%‐58.4%; P < .001) with CCRT and radiation alone, respectively. Subgroup analyses showed a benefit across the majority of subgroups, including patients with oropharyngeal cancer (HR, 0.74; 95% CI, 0.65‐0.85; P < .001). CONCLUSIONS: Concomitant chemoradiation is associated with improved survival for patients with T1‐2N1 HNSCC. Prospective trials in this population should be pursued. Cancer 2017;123:1555–1565. © 2017 American Cancer Society . Abstract : In comparison with radiation alone, concomitant chemoradiation is associated with improved overall survival in patients with T1‐2N1 head and neck squamous cell carcinoma undergoing definitive treatment after adjustments for multiple clinical and demographic factors in multivariate and propensity score–adjusted analyses. Chemoradiation demonstrates a benefit in the majority of subgroups, including patients with oropharyngeal cancer.